Seismic evaluation of masonry structures strengthened with reinforced concrete layers - Ghiassi, Bahman (2012)
Coating the walls with reinforced concrete layers is a conventional method of strengthening masonry structures in Iran. However, due to the lack of analytical and experimental information about the behavior of strengthened masonry wall with this method, the design of these walls is generally conducted based on empirical relations and decisions which may result in uneconomical or under-designed strengthening details. This paper aims at developing a rational method for design and seismic evaluation of unreinforced masonry walls strengthened with reinforced concrete (RC) layers. In the proposed method four failure modes are considered for these walls and the strength relations and acceptance criteria for each of them are provided in accordance with FEMA 356 and ASCE 41 relations for reinforced concrete and masonry walls. The accuracy of the proposed method in predicting the nonlinear behavior and governing failure modes of the strengthened walls is validated by comparing the results with available experimental and performed numerical results.